Suppose you have a differential form $\omega$ written in local coordinates as $$\omega=\sum_{i=1}^ndx_i\wedge dy_i.$$ Can anyone help me showing the following equality: $$\omega^n=n!(dx_1\wedge dy_1\wedge\ldots \wedge dx_n\wedge dy_n).$$ Only as a motivation: the above equality is useful for showing every symplectic manifold is orientable.

  • $\begingroup$ By $\omega^n$ you mean $\omega$ wedged with itself $n$ - times? $\endgroup$ – user38268 Jun 12 '13 at 11:49
  • 1
    $\begingroup$ Try with $n=1$ (it is ok, right?). The case $n=2$ helps you with manipulating the indices. Then use induction and remember that $d x_i \wedge d y_j=- d y_j\wedge d x_i$ $\endgroup$ – Avitus Jun 12 '13 at 11:53
  • $\begingroup$ @O.L., I tried using induction but I lose myself in the calculations.. $\endgroup$ – PtF Jun 12 '13 at 12:25
  • $\begingroup$ @BenjaLim yes, $\omega^n=\underbrace{\omega\times \ldots\times \omega}_{n-times}$. $\endgroup$ – PtF Jun 12 '13 at 12:25
  • $\begingroup$ @Avitus, I'll try.. $\endgroup$ – PtF Jun 12 '13 at 12:26

A motivating example with $n=2$. Let $\omega=dx_1\wedge dy_1 + dx_2\wedge dy_2$ be our 2-form. Then

$\omega\wedge\omega=(dx_1\wedge dy_1 + dx_2\wedge dy_2)\wedge (dx_1\wedge dy_1 + dx_2\wedge dy_2)=dx_1\wedge dy_1\wedge dx_1\wedge dy_1+ dx_2\wedge dy_2\wedge dx_2\wedge dy_2+ dx_1\wedge dy_1\wedge dx_2\wedge dy_2+dx_2\wedge dy_2\wedge dx_1\wedge dy_1$,

where all brackets are removed due to associativity of $\wedge$. Now

$dx_1\wedge dy_1\wedge dx_1\wedge dy_1=-dx_1\wedge dx_1\wedge dy_1\wedge dy_1$


$dx_2\wedge dy_2\wedge dx_2\wedge dy_2=-dx _2\wedge dx_2\wedge dy_2\wedge dy_2$

by antisymmetry of $\wedge$. As $dx_i\wedge dx_i=dy_i\wedge dy_i=0$ (again by antisymmetry!) the two above expressions are euqal to $0$. It remains that

$\omega\wedge\omega= dx_1\wedge dy_1\wedge dx_2\wedge dy_2+dx_2\wedge dy_2\wedge dx_1\wedge dy_1$. But

$dx_2\wedge dy_2\wedge dx_1\wedge dy_1=$(moving twice $dy_2$ to the right) $dx_2\wedge dx_1\wedge dy_1\wedge dy_2=$(moving twice $dx_2$ to the right) $dx_1\wedge dy_1\wedge dx_2\wedge dy_2$.

In summary

$\omega\wedge\omega= 2(dx_1\wedge dy_1\wedge dx_2\wedge dy_2)=2!(dx_1\wedge dy_1\wedge dx_2\wedge dy_2)$,

as wished.

  • $\begingroup$ thanks I'll try to generalizate it =D $\endgroup$ – PtF Jun 12 '13 at 12:44
  • $\begingroup$ if you find the answer useful, you can upvote it and flag it :-) All you need is to remember that "whenever I exchange two symbols $dx$ and $dy$ in the wedge product I get a minus" :-) $\endgroup$ – Avitus Jun 12 '13 at 12:47
  • $\begingroup$ @Avitus +1 for patient explanation $\endgroup$ – Start wearing purple Jun 12 '13 at 12:49

I'd begin by checking (if you haven't already seen this fact) that, even though $1$-forms anticommute, $2$-forms commute. In particular, all the summands $dx_i\land dy_i$ in your $\omega$ commute with each other. So you can multiply out $\omega^n$ without worrying about signs as long as you leave each pair $dx_i$ and $dy_i$ adjacent to each other and in the original order. (In other words, don't change $dx_i\land dy_i$ to $dy_i\land dx_i$, and don't insert any other factors between $dx_i$ and $dy_i$.) When you multiply out $\omega^n$ in this way, a lot of terms have repeated factors; they vanish because (now using anticommutativity) you can move two matching factors next to each other, where they cancel because $dx_i\land dx_i=0$). The surviving terms in $\omega^n$ are those where each of the summands $dx_i\land dy_i$ occurs exactly once as a factor. Each of those terms equals $dx_1\land dy_1\land dx_2\land dy_2\land\dots\land dx_n\land dy_n$ because these summands commute. And there are $n!$ such terms.

  • $\begingroup$ Thanks, I'll try that @Andreas =D $\endgroup$ – PtF Jun 12 '13 at 16:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.